Efforts and challenges in adopting international financial reporting standards (IFRS) in Nigeria - Alkali, Muhammad Yusuf; Lode, Nor Asma (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2012)
Financial reporting in emerging and developed economies has been a challenging debate, due to the frequent changes as well as updates on accounting rules and regulations.Nigeria, being an emerging economy has witnessed a dramatic change and improvement on the accounting reporting since after political development of the country in 1960. The establishment of Nigerian Security Exchange (NSE) in 1982 and the establishment of Nigerian Accounting Standard Board (NASB) in 1984 by the Institute of Chartered Accounting of Nigeria (ICAN) who were the pioneer legislations on the road map to financial reporting in Nigeria. Even though laws and regulations were also issued by the regulatory bodies in Nigeria to ensure quality(value relevance) financial reporting, the level of compliance with the regulations have been very low as reported by the World Bank in the 2004 and 2011(ROSC report).Subsequently, professionals, regulatory bodies and government made the first effort by establishing the road map and the World Bank committee for the adoption of the International Financial Reporting Standards (IFRS) in 2010.Secondly, the formation of the Financial Reporting Council (FRC) in 2011 and FRC training institute in 2012.However, these efforts by the government, World Bank and regulators were faced with the challenges on the development of regulatory and legal framework as well as training of professionals and regulators on the new accounting standard (IFRS).Therefore, this paper explores two main issues: (i) the efforts of government, professional bodies, and regulatory agencies by providing accounting framework and trainings; and (ii) challenges in adopting IFRS due to weaknesses of SAS and unethical behaviours of the preparers of financial statements.